Programmed cell death-ligand 1 (PD-L1) expression in HIV-associated diffuse large B-cell lymphoma – role and regulation - Latib, Zahra (Department of Pathology, 2025)
Diffuse Large B cell Lymphoma (DLBCL) is an aggressive disease that displays striking heterogeneity at both the molecular and clinical levels; and as a result, up to 40% of patients relapse or are refractory to standard first-line therapy. DLBCL is the most common subtype of lymphoma affecting people living with HIV (approximately 50% of all lymphomas seen in this group), and while the introduction of Highly Active Antiretroviral Therapy (HAART) has improved patient outcome, the incidence of DLBCL in this group remains disproportionately high, especially in resource-limited settings. Emerging data indicate that HIV-associated DLBCL, although highly heterogeneous, has distinct clinical, morphological and molecular features from non-HIV-related DLBCL. The complex biology that underpins HIV-associated DLBCL remains largely undefined, necessitating clinical and molecular investigations to identify biomarkers which can be targeted for therapy, specifically within those populations most affected, such as in Sub-Saharan Africa. The programmed death-1/programmed death-ligand 1 (PD-1/PD-L1) signalling pathway is an important immunoregulatory mechanism that dampens the immune response by inhibiting T cell activity, playing a central role in controlling and maintaining tolerance to self-antigens. However, cancer cells have hijacked this mechanism by overexpressing PD-L1 to impair T cell functioning and ultimately escape immune recognition and destruction. Additionally, impairment of this pathway impacts the broader tumour microenvironment (TME), for instance through inhibition of T cell function, creating favourable conditions for tumour progression. In a previous report, PD-L1 levels were shown to be elevated in HIV-positive patients prior to a lymphoma diagnosis, with those harbouring the highest levels of PD-L1 progressing to develop malignancies, suggesting that PD-L1 is a key factor in the onset of lymphoma among HIV-infected individuals. While blockade of the PD-1/PD-L1 pathway with monoclonal antibodies has achieved considerable success in several cancer types, the results remain suboptimal in DLBCL, where the status and relevance of the deregulation of the pathway, and particularly the role and status of PD-L1, remains unclear, and even more so, within an HIV-positive background. This warrants a deeper exploration into the significance of PD-L1 overexpression, as well as the mechanisms influencing PD-L1 expression, in HIV-associated DLBCL. In the current study, three approaches were taken to explore this. Firstly, PD-L1 levels were evaluated and compared within the peripheral blood cell populations of a cohort of newly diagnosed, treatment naïve, HIV-positive and HIV-negative DLBCL patients, using flow cytometry. As per previous observations, HIV-positive DLBCL patients were typically diagnosed at a younger age (64% below the age of 50 years) compared to their HIV-negative counterparts (36% under the age of 50 years). The GCB subtype was the major DLBCL subtype (64%) within the HIV-positive DLBCL group, and a striking 82% of cases had extranodal involvement, reflecting an aggressive/advanced-stage disease. Flow cytometric analysis revealed a significantly higher proportion of PD-L1-positivity overall (CD274+; median: 0.44%; p ≤ 0.01), as well as PD-L1-positive B cells (CD19+ CD274+; median: 6.62%; p ≤ 0.001), in DLBCL patients (irrespective of HIV status), compared to healthy controls. When comparing within the DLBCL patient groups based on HIV status, the HIV-positive cohort displayed a significantly higher proportion of PD-L1-positive cells overall (CD274+; median: 0.65%; p ≤ 0.05), and PD-L1-positive B cells (CD19+ CD274+; median: 10.9%; p ≤ 0.05). No noticeable differences were observed regarding the population of regulatory B cells (CD19+ CD24+ CD38+; median: 57.5% vs 61.2%; p = 0.5344) and PD-L1- positivity within this subset of B cells (CD19+ CD24+ CD38+ CD274+; median: 1.74% vs 0.83%; p = 0.3551) between HIV-negative and HIV-positive DLBCL patients. In the second approach, the status of PD-L1, and T cells and macrophages were evaluated in the TME of HIV-positive and HIV-negative DLBCL tissues, using immunohistochemistry. In concordance with what was observed in the peripheral blood, a higher proportion of PD-L1+ cells were present in the TMEs of HIV-positive DLBCL patients, relative to HIV-negative ones (HIV-positive vs HIV-negative; median: 0.47% vs 0.09%; p ≤ 0.0.5). This was accompanied by reduced CD8+ cytotoxic T cell infiltration (HIV-positive vs HIV-negative; median: 1.25% vs 2.12%; p ≤ 0.0.5), and enhanced CD68+ tumour-associated macrophage infiltration (HIV-positive vs HIV-negative; median: 2.69% vs 1.56%; p ≤ 0.0.5), suggesting differential impairment of the TME in these two groups, and representing a heightened immunosuppressive environment in DLBCL patients infected with HIV. The third approach in this study attempted to delineate the complex relationship between PD-L1, c-MYC, EBNA2 and HIV, using a combination of in silico tools, as well as in vitro analyses using established DLBCL cell lines and models. Using DLBCL gene expression data publicly available on The Cancer Genome Atlas, we found highest expression of PD-L1 to be associated with the ABC subtype. Additionally, an inverse (negative) correlation between PD-L1 and c-MYC expression was observed in patients with this specific subtype of DLBCL. The regulation of PD-L1 by c-MYC was assessed in DLBCL cell lines through an experimental approach, taking HIV and EBV infections into account. In vitro analyses using qPCR and western blotting experiments confirmed this inverse correlation within ABC-derived DLBCL cell lines, as well as within a c-MYC knock-down DLBCL cell model. To investigate the effect of HIV-1 on PD-L1 expression in DLBCL cells, two independent experimental laboratory HIV-1 variants were used, namely aldrithiol-2 inactivated HIV-1, and HIV-1 pseudovirus. Exposure to the virus led to reduced expression of both PD-L1 and c-MYC protein levels, even in the presence of EBNA2, a result which contrasts with our observations using patient derived blood, and tumours. This indicated the importance of studying complex interactions using the appropriate experimental systems. Overall, this study provided novel insights into the status, role and regulation of PD-L1 in DLBCL, specifically within the context of HIV-infection. These findings further confirm that HIV-associated lymphomas harbour unique pathobiological features and provides directions for future basic and clinical research aimed at improving therapeutic approaches specifically tailored for this patient group.